Mathematical analysis of a fractional COVID-19 model applied to Wuhan, Spain and Portugal - Ndaïrou, Faïçal (2021)
We propose a qualitative analysis of a recent fractional-order COVID-19 model. We start by showing that the model is mathematically and biologically well posed. Then, we give a proof on the global stability of the disease free equilibrium point. Finally, some numerical simulations are performed to ensure stability and convergence of the disease free equilibrium point.